CONCENTRATION, DISTRIBUTION AND HEALTH RISK OF HEAVY METALS IN WATER AND BIOTA FROM EKPAN RIVER IN WET SEASON - Nikoro, Omamomo; Okoro, Duke (FUDMA JOURNAL OF SCIENCES, 2025)
This study was aimed at determining the concentration of heavy metals in the surface water and aquatic sentinels from ekpan river and the health risk associated, due to the cumulative effects of industrial pollution, agricultural runoff, and urbanization which has degraded the water quality and disrupt the ecological integrity of this river.The Water samples were collected from upstream, midstream, and downstream sections of the Ekpan River. These samples were analyzed for both physio-chemical parameters, microbial contamination and heavy metals using the Atomic Absorption spectrophotmer (AAS) .Iron and lead levels were highest downstream (1.46 ± 0.26 mg/L and 2.84 ± 0.58 mg/L, respectively), Magnesium and sodium concentrations were elevated upstream (10.31 ± 2.60 mg/L and 49.28 ± 20.83 mg/L, respectively). The Water Quality Index (WQI) indicated severely degraded water quality across all sampling points. The WQI values show a progressive deterioration from upstream (124.56) through midstream (134.89) to downstream (138.23). This pattern is particularly concerning during wet season when dilution effects would typically be expected to improve water quality. The aquatic sentinels (crabs,periwinkles and water hyacinth) were found to contain high concentrations of heavy metals (particularly lead and iron) exceeding standard limits. Overall, among the three aquatic sentinels  (crab,periwinkle,water hyacinth), the periwinkle accumulates the highest levels of heavy metals.During the wet season, periwinkle showed elevated concentrations of Iron (Fe) at 4.817 mg/L and  Manganese (Mn) at 0.841 mg/L, it demonstrates the greatest capacity for heavy metal accumulation, particularly for Iron (Fe) and Manganese (Mn), making it the most affected sentinel.
Keywords: Aquatic Sentinels; Ekpan River; Health Risk